2018
DOI: 10.1038/s41598-018-27956-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association and functional analysis of rs7903456 in FAM35A gene and hyperuricemia: a population based study

Abstract: Recent studies have identified SNP rs7903456 of FAM35A to be associated with gout. Because of the close connections between hyperuricemia and gout, we hypothesized that the effect of rs7903456 on gout might be mediated by hyperuricemia or its related quantitative trait, uric acid level. We investigated the association between 31 SNPs of FAM35A, including rs7903456, and hyperuricemia based on 2,773 hyperuricemia patients and controls. We fitted a simple model for each of these 31 SNPs to screen the candidate SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…These findings demonstrate that the PTPN11 is associated with rheumatoid arthritis and that SHP-2 contributes to the development of rheumatoid arthritis [43]. FAM35A (family with sequence similarity 35 member A), located on chromosome 10, encodes proteins with 835 amino acids and is ubiquitous, including the kidneys and other organs such as thyroid, duodenum, and small intestine [45]. Recently, it was confirmed that rs7903456 of FAM35A was associated with hyperuricemia and gout in Japanese and Chinese populations [7].…”
Section: Plos Onementioning
confidence: 81%
“…These findings demonstrate that the PTPN11 is associated with rheumatoid arthritis and that SHP-2 contributes to the development of rheumatoid arthritis [43]. FAM35A (family with sequence similarity 35 member A), located on chromosome 10, encodes proteins with 835 amino acids and is ubiquitous, including the kidneys and other organs such as thyroid, duodenum, and small intestine [45]. Recently, it was confirmed that rs7903456 of FAM35A was associated with hyperuricemia and gout in Japanese and Chinese populations [7].…”
Section: Plos Onementioning
confidence: 81%